Transitional justice and 'national ownership': an assessment of the institutional development of the war crimes chamber of Bosnia and Herzegovina - Garbett, Claire (Human rights review, 2012)
In anticipation of its closure in 2014, the International Criminal Tribunal for the former Yugoslavia has begun to set out proposals for preserving and promoting its legacy of prosecuting persons responsible for violations of humanitarian law during the conflicts of the 1990s. A key aspect of this legacy has been to support the ‘national ownership’ of the justice systems in the former Yugoslavia that will continue to try war crimes cases in the years to come. This study explores the institutional development of the War Crimes Chamber of the Court of Bosnia and Herzegovina (WCC) to national ownership. In particular, it considers three critical aspects of the WCC's functioning that highlight the challenges that it faces as a mechanism of transitional justice in Bosnia and Herzegovina (BiH). These are the composition of prosecutors and judges, prosecutorial practices and outreach and communication activities. The article shows that the continued difficulties with these areas of legal practice figure as significant obstacles to the WCC's transition to full national ownership by both the legal professionals and local populace of BiH.